Contributions of the electronic record for nursing assistance from the view of the quality audit (Research, Society and Development, 2022)
Objective: to analyze the contribution of the electronic medical record to nursing care in the face of the quality audit. Methodology: integrative literature review carried out in May and June 2022, in the SciELO, Scopus, PudMed, Science Direct, BDENF and BVS databases. Results: the initial search resulted in 500 scientific articles, which titles and abstracts were read, and only 86 were selected for full reading. Of these, 17 articles were selected for answering the research question and three were excluded due to duplicity, resulting in a final sample of 14 articles. Several benefits were observed in the use of electronic medical records for nursing care within the quality audit, highlighting the increase in confidence in sharing the results and recommending solutions, the improvement in the standardization of information and the possibility of performing a quick review. in audits. It was also possible to verify that the use of electronic medical records was associated with a reduction in the risk of medication errors, support for clinical decisions and optimization of work flows and institutional organization. Final considerations: Computerization of health records has a significant impact on improving the safety, efficiency and quality of care, while protecting the privacy and personal rights of the patient. The use of electronic medical records in quality audits represents an invaluable advance for services, as it assists in the standardization of care, service provision and information recording.